Higher concentration of selenium in placental tissues is associated with reduced risk for orofacial clefts. Issue 5 (October 2019) - Pi, Xin; Wei, Yihui; Li, Zhiwen; Jin, Lei; Liu, Jufen; Zhang, Yali; Wang, Linlin; Ren, Aiguo
Summary: Background & aims: Growing evidence suggests that essential trace element imbalance during pregnancy may contribute to fetal malformations, but the role of essential trace elements in the occurrence of orofacial clefts (OFCs) is unknown. We aimed to examine the association between concentrations of zinc (Zn), manganese (Mn), selenium (Se), cobalt (Co), molybdenum (Mo), and nickel (Ni) in placental tissues and the risk for OFCs in offspring in a rural population in northern China with a high prevalence of OFCs. Methods: The case–control study subjects were 103 OFC infants and 206 non-malformed infants. The concentrations of selected trace elements in placental tissues were determined using inductively coupled plasma-mass spectrometry. Sociodemographic information was collected from the mothers through face-to-face interviews using a structured questionnaire. The risk for OFCs in association with higher concentrations of the trace elements was estimated using the odds ratio (OR) with its 95% confidence interval (95% CI). Results: The placental median concentrations of Se and Ni were significantly lower, but those of Mo were significantly higher in OFC cases than in controls (all P  < 0.05). A Se concentration above the median of all subjects was associated with a 58% reduced risk for OFCs (adjusted OR 0.42, 95% CI 0.23, 0.77) after adjusting for potential confounding factors. The risk for OFCs decreased with increases in placental Se concentrations, with adjusted ORs of 0.45 (95% CI 0.22, 0.92) for the second tertile and 0.22 (95% CI 0.10, 0.49) for the top tertile of Se concentration, with the lowest tertile concentration as the referent ( P trend  < 0.001). No association was observed between placental Zn, Mn, Co, Mo, or Ni concentration and risk for OFC. Conclusions: The concentration of Se in placental tissues was dose-dependently associated with decreased risk for OFCs in offspring. This finding suggests that maternal Se intake during pregnancy may protect against OFCs in offspring.